South African youth's understanding of feelings, thoughts and behaviours: Implications for the development of CBT-based mental health interventions. Issue 5 (7th September 2022) - Human, Suzanne; Gericke, Hermine; Loades, Maria; Stallard, Paul; Coetzee, Bronwynè J.
Abstract: Background: Mental health problems are common in youth in low- and middle-income countries (LMICs), including South Africa. Preventative interventions, based on cognitive behaviour therapy (CBT), delivered in schools, have been found to alleviate symptoms of depression and anxiety in high income countries (HICs). However, less is known about whether youth in LMICs are able to engage with the core concepts of CBT. Aims: To explore how young people in the Western Cape, South Africa, understand key CBT concepts, such as feelings, thoughts and behaviours. Method: We interviewed 22 young people (10–15 years of age; mean age 11.6 years; SD = 1.0) recruited from two public primary schools in the Western Cape, South Africa. Interviews were audio-recorded, transcribed verbatim, translated from Afrikaans into English where necessary and analysed thematically using a deductive approach. Results: Young people described feelings as internal, private, and should only be shared with trusted others. They also described how feelings varied, depending on the situation. They found the concept of thoughts more challenging to describe. Youth were able to say what they do when they experience unpleasant feelings, and they linked their behaviours to their feelings and thoughts. Conclusions: In this cultural context, our qualitative investigation found evidence that young people were able to engage with abstract concepts including feelings and to some degree, thoughts. To ensure that CBT-based interventions are developmentally appropriate and accessible, psychoeducation may help youth distinguish between thoughts, feelings and behaviours, and a focus on identifying and naming feelings may be beneficial.